The Paleochrono-1.1 probabilistic model to derive a common age model for several paleoclimatic sites using absolute and relative dating constraints - F. Parrenin; M. Bouchet; C. Buizert; E. Capron; E. Corrick; R. Drysdale; K. Kawamura; A. Landais; R. Mulvaney; I. Oyabu; S. O. Rasmussen (Geoscientific Model Development)
Past climate and environmental changes can be reconstructed using paleoclimate archives such as ice cores, lake and marine sediment cores, speleothems, tree rings, and corals. The dating of these natural archives is crucial for deciphering the temporal sequence of events and rates of change during past climate changes. It is also essential to provide quantified estimates of the absolute and relative errors associated with the inferred chronologies. However, this task is complex since it involves combining different dating approaches at different paleoclimatic sites and often on different types of archives. Here we present Paleochrono-1.1, a new probabilistic model to derive a common and optimized chronology for several paleoclimatic sites with potentially different types of archives. Paleochrono-1.1 is based on the inversion of an archiving model: a varying deposition rate (also named growth rate, sedimentation rate or accumulation rate) and also (for ice cores) a lock-in depth of air (since, in the absence of significant surface melt, the air is trapped in the ice at about 50–120 m below the surface) and a thinning function (since glacier ice undergoes flow). Paleochrono-1.1 integrates several types of chronological information: prior knowledge of the archiving process, independently dated horizons, depth intervals of known duration, undated stratigraphic links between records, and (for ice cores) Δdepth observations (depth differences between events recorded synchronously in the gas and solid phases of a certain core). The optimization is formulated as a least-squares problem, assuming that all probability densities are near-Gaussian and that the model is nearly linear in the vicinity of the best solution. Paleochrono-1.1 is the successor of IceChrono, which produces common and optimized chronologies for ice cores. Paleochrono-1.1 outperforms IceChrono in terms of computational efficiency, ease of use and accuracy. We demonstrate the ability of Paleochrono-1.1 in an experiment involving only the MSL speleothem in Hulu Cave (China), and we compare the resulting age model with the Speleothem Isotope Synthesis and Analysis version 2 (SISALv2) age models. We then demonstrate the multi-archive capabilities of Paleochrono in a new ice-core–speleothem dating experiment, which combines the Antarctic Ice Core Chronology 2023 dating experiment, based on records from five polar ice cores, with data from two speleothems from Hulu Cave, dated using uranium / thorium radiometric techniques. We analyze the performance of Paleochrono-1.1 in terms of computing time and memory usage in various dating experiments. Paleochrono-1.1 is freely available under the open-source MIT License.